2021
DOI: 10.1111/bpa.12925
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated GPR30 expression in the epileptogenic foci of female patients with focal cortical dysplasia type IIb and tuberous sclerosis complex is correlated with 18F‐FDG PET‐CT values

Abstract: Focal cortical dysplasia type IIb (FCDIIb) and tuberous sclerosis complex (TSC) are typical causes of developmental delay and refractory epilepsy. G-protein-coupled receptor 30 (GPR30) is a specific estrogen receptor that is critical in neurodevelopment, neuroinflammation, and neuronal excitability, suggesting that it plays a potential role in the epilepsy of patients with FCDIIb and TSC. Therefore, we investigated the role of GPR30 in patients with FCDIIb and TSC. We found that the expression of GPR30 and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…TLR2, TLR4 and their endogenous ligand HMGB1 are highly expressed in MCDs and further activate NF-κB signaling through the TRIF pathway (Wang et al 2018). Our previous studies also showed that the NF-κB pathway was signi cantly activated in the epileptogenic foci of patients with MCDs (Wang et al 2021). These studies suggest that in ammation persists in MCDs, and active in ammatory resolution fails to extinguish this in ammation.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…TLR2, TLR4 and their endogenous ligand HMGB1 are highly expressed in MCDs and further activate NF-κB signaling through the TRIF pathway (Wang et al 2018). Our previous studies also showed that the NF-κB pathway was signi cantly activated in the epileptogenic foci of patients with MCDs (Wang et al 2021). These studies suggest that in ammation persists in MCDs, and active in ammatory resolution fails to extinguish this in ammation.…”
Section: Discussionmentioning
confidence: 89%
“…The mean optical density (MOD) of FPR2 was determined according to a previous report (Wang et al 2021). Brie y, the stained sections were assessed using a light microscope (BX51, Olympus, Japan).…”
Section: Evaluation Of Immunostainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The product of the intensity and frequency score was calculated as the IR score. In addition, the mean optical density (MOD) of FPR2 was calculated using the same procedure as given in a previous study 30 . The photographs and MOD were analyzed with Image‐Pro Plus software (Media Cybernetics).…”
Section: Methodsmentioning
confidence: 99%
“…Slice preparation and electrophysiological recordings were performed in a similar way to our previous study. [13] Control or TLE mice were anesthetized with phenobarbital sodium (60 mg/kg, i.p.) and the brains were rapidly decapitated, removed and placed in an ice-cold sucrose-based dissecting solution (in mM): sucrose (300), KCl (2), NaH 2 PO 4 (1.25), CaCl 2 (1), MgCl 2 (5), NaHCO 3 (26) and glucose (11).…”
Section: Electrophysiological Recordingmentioning
confidence: 99%